2011
DOI: 10.1007/978-3-642-19805-2_14
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing Deterministic Lattice Automata

Abstract: Abstract. Traditional automata accept or reject their input, and are therefore Boolean. In contrast, weighted automata map each word to a value from a semiring over a large domain. The special case of lattice automata, in which the semiring is a finite lattice, has interesting theoretical properties as well as applications in formal methods. A minimal deterministic automaton captures the combinatoric nature and complexity of a formal language. Deterministic automata are used in run-time monitoring, pattern rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Specifically, we used the fact that states in such a DFA have separating words. It is known that there is no canonical minimal LDFA for a lattice language [22]. However, we show below that it is possible to assume that the specification is given by means of an LDFA whose states have separating words.…”
Section: Separable Ldfasmentioning
confidence: 91%
See 3 more Smart Citations
“…Specifically, we used the fact that states in such a DFA have separating words. It is known that there is no canonical minimal LDFA for a lattice language [22]. However, we show below that it is possible to assume that the specification is given by means of an LDFA whose states have separating words.…”
Section: Separable Ldfasmentioning
confidence: 91%
“…An exception is the problem of minimization of LDFAs, which is NP-complete [22]. It is shown in [22] that there is no canonical minimal LDFA for a latticed language.…”
Section: Computation-based Costmentioning
confidence: 99%
See 2 more Smart Citations
“…In [13], we studied the minimization problem for LDFAs. We showed that it is impossible to define a right congruence in the context of latticed languages, and that no canonical minimal LDFA exists.…”
Section: Introductionmentioning
confidence: 99%